Study on growth traits at weaning and yearling stages of indigenous and F1 crossbred buffalo in Bangladesh - Shahjahan, Md; Khatun, Asma; Khatun, Sumya; Hoque, Md Mahbubul; Hossain, Sohrab; Huque, Quazi M Emdadul; Awal, Tabith M; Mintoo, Abdul Awal (Asian Journal of Medical and Biological Research, 2018)
This study was planned to clarify the variation of body weight and average daily gain traits in both indigenous and F1 crossbreed (Local×Mediterranean) buffalo at weaning (sixth month) and yearling stages (twelfth month). Data were collected from 33 indigenous and 35 F1 crossbred buffalo progeny during the period of 2011 to 2014 with intensive management system at Research and Development farm of Lal Teer Livestock Limited in Bangladesh. The gathered data were analyzed using general linear model (GLM) and independent sample t test. The effect of parity, sex, season and breeding year on body weight and average daily gain were observed where significant values found in breeding period (p <0.01) of crossbred buffalo for body weight. It might be the reason of crossbreeding to indigenous buffalo cows using imported semen with better genetic merit. The parity (p <0.05), season (p <0.05) and breeding period (p <0.01) were also significant for average daily gain measurement which suggesting environmental adaptability beside additive genetic effects. Body weights were measured at weaning and yearling stages for both local (113 to 195 kg) and F1 crossbred (144 to 220 kg) buffalo progeny to screen the elite offspring for the Genetic Farm and Bull station. Similarly, average daily gain observed 469 to 457 g and 600 to 506 g at the previously mentioned two stages for both local and F1 buffalos, respectively. It was observed that studied traits were comparatively better in F1 buffalo progeny than indigenous. The comparison of average daily weight gains between indigenous and F1 buffalos at weaning and yearling periods showed significant differences for body weight (p <0.001) and average daily gain (p <0.05), respectively. It is concluded that genetic gain might be possible in local buffalo population by grading up process which could switch the traditional buffalo rearing to commercial level as well as meeting the nutritional demand of country people. Asian J. Med. Biol. Res. December 2017, 3(4): 499-503